Standard pressure deposition of crack-free AlN buffer layer grown on c-plane sapphire by PALE technique via MOCVD - Abd Rahman, Mohd Nazri; Shuhaimi, Ahmad; Yusuf, Yusnizam; Li, Hongjian; Sulaiman, Abdullah Fadil; Alif Samsudin, Muhammad Esmed; Zainal, Norzaini; Abdul Khudus, Muhammad Imran Mustafa (Elsevier, 2018)
A high-quality aluminium nitride buffer layers were grown on (0 0 0 1) sapphire substrate at standard pressure with a subsequent low growth temperature via metal organic chemical vapour deposition. The preparation of aluminium nitride buffer layers was accomplished by growing a thin aluminium nitride nucleation layer through a nominal growth condition followed by depositing a thick aluminium nitride film using pulsed atomic-layer epitaxy technique. In 13.3 kPa ambient, the influence of aluminium nitride nucleation layer on the crystal quality of the aluminium nitride film atop was studied by varying the nucleation layer growth temperature at 700, 800, 900, 1000 and 1100 °C, respectively. It was observed that the growth temperature of nucleation layer substantially affected the structural properties of the top aluminium nitride film where the lowest value for symmetric (0 0 0 2) and asymmetric (1 0–1 2) x-ray rocking curve analysis were achieved at 1100 °C, indicating the reduction of dislocation density in the aluminium nitride films. In line with that, this result was sustained by the root mean square surface roughness evaluated via atomic force microscopy. Moreover, an atomically-flat crack-free aluminium nitride buffer layer was demonstrated by field emission scanning electron microscopy measurement.